2022-RA-1149-ESGO Oxaliplatin-based treatments are currently a valid therapeutic option in heavily pretreated ovarian cancer patientswith hypersensitivity reactions (HRs) to carboplatin in the antiangiogenics and PARPi era. (20th October 2022) - Inoa, Jennifer Olalla; Escudero, Laura Sanchez; Manzano, Aranzazu; Marquina, Gloria; Coronado, Pluvio; Garcia-santos, Francisco Javier; Bellon, Monica; Morillas, Leticia Sanchez; Rivas, Montserrat Fernandez; Fernandez, Ramiro Mendez; Segura, Pedro Perez; Casado, Antonio
Abstract : Introduction/Background: Oxaliplatin, in the era prior to antiangiogenics and PARPi therapies, demonstrated activity in patients (pts) with ovarian cancer (OC) in phase I, II and III studies. Oxaliplatin may play a role in pts with hypersensitivity reactions (HRs) to carboplatin. Methodology: Single-institution retrospective experience (2004–2022) in terms of efficacy and safety with oxaliplatin in recurrent OC, especially in pts with HRs to carboplatin.SPSS version 22.0 was used for statistical analyses Results: 68 pts were treated with oxaliplatin (monotherapy, 25%, in combination 75%, mostly with gemcitabine (56.4%) or paclitaxel (15, 1%). Pts and disease characteristics are shown in Table 1 . Median progression free survival (mPFS) and overall survival (mOS) were 3 and 13 months (m), respectively. There was no difference between platinum-resistant and platinum-sensitive in terms of PFS, but there was a benefit in mOS in platinum-sensitive disease (13 vs 6 m). Pts who attained controlled disease with oxaliplatin showed a mPFS of 6 months and mOS of 15 months. 45.9% of patients had experienced prior HRs to carboplatin; 67% of them did not require desensitization to oxaliplatin. However, 17.8% of the patients suffered HRs to oxaliplatin. PARPi before oxaliplatin was used in 5 pts. Of them, two stable diseases were achieved with no objective responses. Pts with clinical benefit to oxaliplatin and who had received prior bevacizumab had a 64% lower risk of progression (HR 0.36 IC 95% 0.169–0.800, p 0.012), and patients with no benefit from oxaliplatin had a better outcome with the previous use of bevacizumab (HR 0.20, IC 95% 0.064 – 0.679, p=0.009). Grade 3/4 toxicity was observed in 36.8%, mainly hematological and gastrointestinal toxicity. Conclusion: Oxaliplatin improves PFS and OS in pts with OC recurrent setting, in particular in those pts not candidates to receive carboplatin-based regimens mainly due to HRs. Oxaliplatin is currently a valid treatment.